Capital Expansion, Endogenous Growth and Equilibrium Unemployment - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 1998)
A model is developed, which captures the interactions of unemployment and economic growth in general equilibrium. The economy evolves along a correct-expectations equilibrium path exhibiting endogenous job rationing, and productivity growth is driven by installation of new capital. Under the maintained hypothesis that the elasticity of substitution between capital and labour is less than unity, unemployment benefits are shown to shift up the whole path of equilibrium unemployment, leaving the economy with a higher natural rate of unemployment and lowering the long-run growth rate permanently. Investment tax credits financed by lump sum taxes on total income are capable of lowering the natural rate and raising the economy's growth rate.